Signal Recognition Particle in Human Diseases - Kellogg, Morgana K.; Tikhonova, Elena B.; Karamyshev, Andrey L. (Frontiers in Genetics, 2022)
The signal recognition particle (SRP) is a ribonucleoprotein complex with dual functions. It co-translationally targets proteins with a signal sequence to the endoplasmic reticulum (ER) and protects their mRNA from degradation. If SRP is depleted or cannot recognize the signal sequence, then the Regulation of Aberrant Protein Production (RAPP) is activated, which results in the loss of secretory protein mRNA. If SRP recognizes the substrates but is unable to target them to ER, they may mislocalize or degrade. All these events lead to dramatic consequence for protein biogenesis, activating protein quality control pathways, and creating pressure on cell physiology, and might lead to the pathogenesis of disease. Indeed, SRP dysfunction is involved in many different human diseases, including: congenital neutropenia; idiopathic inflammatory myopathy; viral, protozoal, and prion infections; and cancer. In this work, we analyze diseases caused by SRP failure and discuss their possible molecular mechanisms.